BREEDING EXPERIMENT OF SPINY SEAHORSE (HIPPOCAMPUS SPINOSISSIMUS 1913) IN THE SEA OF KHANH HOA PROVINCE - Hoa, Ho Thi; Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2009)
Spiny seahorse (Hippocampus spinosissimus) was the first time bred successfully in capture condition. The pregnant male from the wild were collected and reared in glass tank with aeration and fed on frozen small shrimp twice daily. Newborn juveniles were separately reared in open aquaculture system with density of 3 individuals/liter. Within the first two weeks, the juveniles were fed on live Copepods twice daily with density of 3-5 individuals/ml. Then, I 5-day old juveniles were weaned with frozen Mysids and switched to cutting frozen Acetes twice dail). The results showed that survival of two-month old juveniles was 48.83 ± 12.37%. The length and weight of two-month old juveniles were 55.76 ± 3.50mm and 0.76 ± 0.06g, respectively). Absolute growth rate of one-month old and two-month old juveniles were 0.98 and 1.60mm/day. respectively.